2004
DOI: 10.1111/j.1365-263x.2004.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of early childhood caries among First Nations children, District of Manitoulin, Ontario

Abstract: Our results indicate that dental caries and ECC are highly prevalent in this population, with ECC cases having 6.7 more dmft than non-cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2
15

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 15 publications
9
45
2
15
Order By: Relevance
“…Surveys conducted in Alaska, Canada and Greenland in the early 1900s present traditional lifestyles resulting in minimal caries and little tooth loss, even into old age, and as southern cariogenic foods were brought north, diets changed, contributing to increased levels of disease. Recent work in other Arctic and Indigenous populations confirm this pattern (11)(12)(13)(14)(15)(16)(17). The Maori in New Zealand, Aborigines in Australia, Sami in northern Scandinavia, and Indigenous groups in Central and South America and East Asia, all report a significant decline in oral health sustained post-colonisation.…”
Section: Determing Health and Disease In Inuit Populationsmentioning
confidence: 65%
“…Surveys conducted in Alaska, Canada and Greenland in the early 1900s present traditional lifestyles resulting in minimal caries and little tooth loss, even into old age, and as southern cariogenic foods were brought north, diets changed, contributing to increased levels of disease. Recent work in other Arctic and Indigenous populations confirm this pattern (11)(12)(13)(14)(15)(16)(17). The Maori in New Zealand, Aborigines in Australia, Sami in northern Scandinavia, and Indigenous groups in Central and South America and East Asia, all report a significant decline in oral health sustained post-colonisation.…”
Section: Determing Health and Disease In Inuit Populationsmentioning
confidence: 65%
“…Algunos autores sugieren que más del 12% de los niños en edad preescolar están afectados, aunque en ciertas poblaciones la afección es tan alta que alcanza un 70%. [6][7][8][9] Los niños con esta entidad tienden a mantener un riesgo alto de sufrir caries dental en la dentición permanente. 10 La salud oral de los niños se encuentra muy relacionada con el periodo gestacional de la madre, ya que las alteraciones que se presentan durante este periodo pueden afectar la salud buco dental del hijo, es evidente la importancia de que el personal médico tenga los conocimientos necesarios, para establecer programas preventivos, además de detectar las enfermedades orales más frecuentes y de esta manera orientar y remitir al paciente donde el odontólogo.…”
Section: Introductionunclassified
“…The differentials between Indigenous and non-Indigenous dental disease experience were marked, with Indigenous children in the least socially disadvantaged categories frequently having worse oral health than non-Indigenous children in the most disadvantaged categories and rural Indigenous children having up to three and a half times the dental disease experience of rural-dwelling nonIndigenous children. The literature shows that Indigenous children in countries such as New Zealand, Canada and the USA also experience poorer oral health than their non-Indigenous counterparts (Jones et al 1992;Caplan & Weintraub 1993;Thomson 1993;Niendorff & Jones 2000;Edelstein 2002;Lee & Dennison 2004;Peressini et al 2004). Although our sample size was large, it is important to consider its representativeness when considering the study's merits.…”
Section: Discussionmentioning
confidence: 99%
“…The role of residential location in Indigenous child oral health is recognised. Endean et al (2004) found that remote Indigenous children had markedly higher dental disease levels in comparison with the general Australian child population, and among Indigenous populations in Canada and the USA, rural-dwelling children have been consistently found to have poorer oral health than those residing in urban areas (Jones et al 1992;Caplan & Weintraub 1993;Niendorff & Jones 2000;Edelstein 2002;Peressini et al 2004). School dental service provision to rural areas in Australia, including oral health education and promotion initiatives, varies depending upon location, logistical challenges and staff availability (NHC 2001).…”
Section: Discussionmentioning
confidence: 99%